DESCRIPTION OF BABY BLUES SYMPTOMSIN POSTPARTUM MOTHER BASED ON CHARACTERISTICS IN dr. SLAMET GARUT HOSPITAL IN 2018 - Iceu Mulyati (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2019)
The phenomenon of the murder case carried out by a mother, 27 years old for her child, which is 4 months old on October 23, 2017 in Karangpawitan Garut, The research design is descriptive. Univariate data analysis. The population postpartum mothers who gave birth at Dr. Slamet Garut in June 2018 as many as 68 people. The sampling was purposive sampling.samples made by respondents was 41 people. The results showed that mothers who experienced baby blues symptoms based on the age of <20 years 53.8%, primiparous parity as 61.5%, the types of labor with the action 69.2%,the working mothers 92.3%, The baby blues were seen from the age of <20 years because not ready mentally, primipara parity because did not have experience, labored with action because felt unable to give birth to a normal baby and working mothers who thought too much about the burden at home and on workplace. Conclusion that mothers with age <20 years, primiparous parity, childbirth with action and mothers who work at high risk experience baby blues. Suggestions for health workers to be able to provide health counseling regarding maternal and infant care at home and mothers can discuss with friends or health workers.